Choosing Death : Suicide and Calvinism in Early Modern Geneva - Watt, Jeffrey R. (Jeffrey Rodgers), 1958- (Book collections on Project MUSE., 2001)
In this case study of the Republic of Geneva, Jeffrey R. Watt convincingly argues the early modern era marked decisive change in the history of suicide. His analysis of criminal proceedings and death records shows that magistrates of the sixteenth and early seventeenth centuries often imposed penalties against the bodies and estates of those who took their lives.